THE EFFECT OF INFLATION ON THE COMPUTATION OF INCOME OF PUBLIC UTILITIES. - Bierman, Harold (The Accounting Review, 1956)
Abstract The author discusses the effects of inflation on the income of public utilities. He gives an introduction to the scenario of measuring corporate income following the inflation resulting from the world wars. He makes an attempt to measure the amount of the overstatement of income for the electric utility industry and fourteen individual companies. In studying the electric utility industry, he illustrates the adjustments made to depreciation charges in Table 1. He discusses over-statement of income and decrease in the real income of electrical utilities after converting them into dollars, using Table 2. He then enumerates the factors which give rise to the margin of error in assessing income. He explains the procedures followed in studying fourteen individual companies in face of certain defects in the study of the electrical utility industry. In Table 3, the author presents confirmation to the conclusions indicated in the study of the electrical utility industry, and a comparison of the operating adjusted income author shows that the results of the years 1940 and 1953, in Table 4, while in Table 5, the depreciation adjustment is not proportional to the depreciation charge. He presents a comparison between public utilities and other industries.